Gender Dysphoria and Scoliosis: Pediatric Orthopaedists Are Very Much Members of the Healthcare Team - Eden N. VanderHoek, BS; Jung U. Yoo, MD; Natalie L. Zusman, MD (Elsevier, 2024)
Background: Adolescence is a pivotal time of change, and in treating adolescent idiopathic scoliosis (AIS), pediatric orthopaedists form lasting relationships with adolescents. Gender dysphoria (GD) also affects a significant number of adolescents, and with high rates of mental health disorders seen in both GD and AIS, the pediatric orthopaedic surgeons can play an important role in recognizing psychological challenges present in those patients with concurrent AIS and GD. Methods: A national database investigation was performed using PearlDiver Technologies, Inc., queried for AIS and GD using the International Classification of Diseases codes in patients aged 10-18 years in the period of October 2015 through 2020. Psychological disorders of interest included anxiety, depression, suicidal ideation, and suicide attempt. Descriptive statistics and chi-squared analyses were performed comparing the prevalence of psychological disorders between cohorts of AIS ​+ ​GD patients, AIS-only patients, and GD-only patients. Additionally, mental health outcomes were compared based on the presence or absence of bracing and fusion interventions for AIS between the AIS ​+ ​GD and AIS-only cohorts. Results: Over the 12-year study period, 820 adolescent patients were identified as having concurrent AIS and GD, representing 0.32% of adolescent AIS patients in the database. In the population with both AIS and GD, diagnoses of mental health issues were observed to be more common across the evaluated parameters. Depression was 7-fold more common (22.2% vs. 3.6%), anxiety 3-fold (79.0% vs. 25.9%), suicidal ideation 12-fold (36.2% vs. 3.8%), and suicidal attempt nearly 13-fold (5.1% vs. 0.4%, P ​< ​.01 for all, AIS ​+ ​GD and AIS only, respectively). Of all included parameters, only suicidal ideation was significantly different between the AIS ​+ ​GD and GD-only cohorts (36.2% vs. 41.7%). No significant differences in psychological disorders were present between AIS ​+ ​GD patients and AIS-only patients based on treatment interventions; however, significant differences were present between groups relative to presence or absence of GD. Conclusion: While the overall occurrence of adolescents diagnosed with both GD and AIS is low, those with both conditions exhibit notably higher rates of psychological comorbidities than those with AIS alone. Comorbidities in AIS ​+ ​GD were not, however, significantly different from those in the GD-only population. The findings emphasize the importance of mental health awareness by pediatric orthopaedists, especially in the context of patients additionally struggling with GD-associated manifestations. Key Concepts: (1) The frequency of mental health diagnosis is high in both the adolescent idiopathic scoliosis (AIS) and gender dysphoria (GD) populations. Mental health diagnoses range from 3- to 13-fold greater in the AIS ​+ ​GD compared with AIS-only patients. (2) Bracing can be challenging to the mental health of AIS patients and thus may present an even greater issue in patients with AIS ​+ ​GD. (3) Pediatric orthopaedists have a longitudinal relationship with AIS patients and therefore should have a heightened awareness of the complexities of patients with AIS ​+ ​GD. Level of Evidence: III.